Isolation of lactic acid bacteria and quantification of Lentilactobacillus buchneri using qPCR in sorghum silage inoculated with native strains in tropical conditions - JOÃO PAULO S. ROSEIRA; ODILON G. PEREIRA; TÂMARA C. DA SILVEIRA; RICARDO M.A. PINHO; RENAN S. CASCARDO; ROSINEA A. DE PAULA; POLIANE A. ZERBINI; HILÁRIO C. MANTOVANI; WAGNER S. ALVES; KARINA G. RIBEIRO (Anais da Academia Brasileira de Ciências)
Abstract The objective of this study was to isolate lactic bacteria, quantify the population of Lentilactobacillus buchneri by qPCR, and evaluate the effects of the inoculation of native strains of L. buchneri in sorghum silage. The treatments were arranged in a 4 × 5 factorial scheme, with four inoculants (I) and five fermentation periods (P) (7, 14, 28, 45, and 90), in a completely randomized design, with three replicates. Forty-seven LAB strains were isolated from control silage, and L. buchneri was the predominant species at 45 and 90 days of fermentation. The qPCR data showed that L. buchneri predominated during all fermentation periods in the inoculated silages. There was an effect (P<0.05) of I × P interaction on all studied variables of the fermentative profile and microbial population. There was an effect (P<0.05) of I × P interaction on the dry matter (DM), neutral detergent fiber (NDF), in vitro DM digestibility, and in vitro NDF digestibility. Inoculation with L. buchneri resulted in silages with better fermentative quality and digestibility and a lower yeast population. The native LB.1 and LB.4 strains have potential to be used as inoculants in sorghum silage production, with effects on fermentation quality at 45 days of storage.